eHealth and Remote Monitoring - Hajjam El Hassani, Amir (IntechOpen, 2012)
eHealth initiatives, many of which are being undertaken in countries around the globe, have myriad benefits, including improvement of coordination and integration of health care delivery, empowerment of individuals and families for helping them manage their own health better and prepare health care plans, and facilitation of public health initiatives. eHealth are not simply a technology but a complex technological and relational process. In this sense, clinicians and health care providers who seek to successfully exploit eHealth should pay special attention to technology, ergonomics, human factors, and organizational changes associated with the structure of the relevant health service. This book gives an overview of the impact of eHealth systems on access to health care, quality of information on health care, cost-effectiveness of health care services and the development of eHealth equipment.